The effects of advanced spectral line shapes on atmospheric carbon dioxide retrievals. (November 2022) - Long, D.A.; Adkins, E.M.; Mendonca, J.; Roche, S.; Hodges, J.T.
Highlights: Advanced spectroscopic line shape models are required in the analysis of accurate laboratory and field observations of molecular spectra. Incorporation of advanced line shape models in atmospheric greenhouse gas retrieval algorithms led to reduced bias in measured air mass. Uncertainties in atmospheric temperature gradients limit the accuracy of column profile retrievals. Abstract: Line shape effects such as speed-dependence and collisional (Dicke) narrowing are manifest in high signal-to-noise ratio laboratory spectra for a wide range of molecular species and sample conditions. However, these effects are usually neglected in spectroscopic models used in remote sensing of atmospheric greenhouse gases. Here we examine the effects of line profile choice on laboratory spectra and XCO2 values retrieved from Total Carbon Column Observing Network (TCCON) spectra. To this end, we utilize limiting cases of the Hartmann-Tran profile (HTP) with shape parameters recently measured by cavity ring-down spectroscopy. Significant differences highlighting the importance of including speed-dependence effects in forward models were observed both in scaling retrievals as well as profile retrievals. However, because of uncertainties associated with the atmospheric temperature gradient, it was not possible to extract accurate carbon column profiles even with inclusion of these new line shape parameters and advanced line profiles.